Sterile Insect Technology for Pest Control in Agriculture - Maru, Nitesh Kumar; Sao, Yushma (International Journal of Bio-resource and Stress Management, 2018)
Insects are known to cause significant damage to crops and affect agricultural productivity. Loss of major crops due to insect pest varies between 10 and 30%.The indiscriminate use of broad-spectrum insecticides has caused major problems with pest resistance, residues in food, environmental contamination, outbreaks of secondary pests, and reductions in populations of beneficial insects. Humans are exposed to such chemicals while still in the womb of the mother. Therefore, human life would be threatened not only directly by pesticides in environment, but indirectly by contaminated food chain. These developments combined with the mounting awareness of the general public, have increased demands for pest control methods that are both efficient and friendly to the environment. A very powerful method for integration in IPM programs as a final eradication component is the sterile insect technique (SIT).This genetic control method exploits the insect’s mate-seeking expertise to introduce genetic abnormalities into the wild population. In view of the increasing demand of environmental-friendly control tactics, it is anticipated that the SIT, will increasingly gain an importance in the years/decades to come in India, as BARC Mumbai is working on potato tuber moth (Phthorimaea operculella) and red palm weevil (Rhyncophorus ferrugineus); Delhi University, Dept. of Zoology is working on Tobacco caterpillar (Spodoptera litura); UAS RAICHURis working on Red gram Webber (Maruca vitrata). Hence this article discuss a critical overview of its principles/practice, need for further research, development, and application for the pest control in agriculture.